Precesarean Prophylactic Balloon Catheters for Suspected Placenta Accreta: A Randomized Controlled Trial. Issue 5 (November 2015) - Salim, Raed; Chulski, Alexander; Romano, Shabtai; Garmi, Gali; Rudin, Michael; Shalev, Eliezer
Abstract : OBJECTIVE: To examine the effect of prophylactic balloon catheters on bleeding morbidity among women with a prenatal diagnosis of placenta accreta. METHODS: In a randomized trial, women with a prenatal diagnosis of placenta accreta were randomized to either preoperative prophylactic balloon catheters (intervention group) or to a control group. Other than placement of the prophylactic balloon catheters in the anterior division of the internal iliac arteries, the same multidisciplinary approach was used in both groups. The primary study outcome was the number of packed red blood cell (RBC) units transfused. To detect a mean reduction of three packed RBC units with the prophylactic balloon catheters, 12 women in each group were needed. RESULTS: Between January 2009 and March 2015, 27 women were randomized: 13 in the intervention group and 14 in the control group. Demographic and obstetric characteristics were similar between the groups. Six (46.2%) women in the intervention and seven (50.0%) in the control group underwent cesarean hysterectomy ( P =.84). There were no significant differences between the intervention and control groups in the mean number of packed RBC units transfused, 5.2 (±6.2) and 4.1 (±3.8), respectively ( P =.90), or in the calculated blood loss, 4, 950 (±5, 051) and 4, 709 (±3, 434) mL ( P =.72). The number of women with blood loss greater than 2, 500 mL, number of plasma products transfused, duration of surgery, peripartum complications, and hospitalization length did not differ significantly between the groups. Reversible adverse effects related probably to prophylactic balloon catheter insertion were noted in 2 of 13 (15.4%) women. CONCLUSION: In women with preoperative suspicion of placenta accreta, preoperative placement of prophylactic balloon catheters did not affect the number of packed RBC units transfused. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, www.clinicaltrials.gov, NCT01373255. LEVEL OF EVIDENCE: I Abstract : When placenta accreta is suspected, preoperative placement of prophylactic balloon catheters does not affect maternal bleeding morbidity.